(untitled) (Research, Society and Development, 2021)
Objective: To analyze the impact of academic-pedagogical actions on the formation of Nursing students to act in the world of work. Method: This was a qualitative study, conducted at two federal universities in Rio de Janeiro. Forty-three graduates participated, and a semistructured interview script was applied to them from June to September 2016. For data processing, we opted for lexical/textual analysis, using the software IRAMUTEQ (Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires), allowing two types of interpretation of results: frequency and word network. Results: Two themes were captured: practical experiences and the protagonism of the residency course; and weaknesses of the formation. Conclusion: It was found that the theory-practice relationship needs to be strengthened, and must happen in an articulated manner, through successive approximations with the working reality, going through a growing experience that allows deepening the experiences of being a nurse.